DIPLOMASI MULTILATERAL IRAN DALAM UPAYA PENCABUTAN SANKSI DEWAN KEAMANAN PBB (Pada Masa Presiden Hassan Rouhani) - Halifa Haqqi, Christian Adiyudha, Setyasih Harini & (Transformasi, 2016)
The development of iran‟s nuclear program was the alternate way to fullfill the energy supply ofIran. With the development of nuclear, Iran government need to achieve national interest whichis independency of energy for the people of Iran. Iran‟s effort to increase nuclear developmentmade the security council of UN give the punishment for Iran nuclear program. With theinternational punishment, Iran government using diplomacy and negotiation to solve the nuclearproblem. By using negotiation with P5+1 group, Iran hoping the nuclear program problem wasbeing solve. With doing join negotiation between Iran and P5+1 group showing the commitmentfrom Hassan Rouhani government to ending the program nuclear problem and to take theinternational punishment with agreement of conclusion on negotiation with P5+1 group. Byusing the national interest theory, diplomacy, and Multilateral diplomacy, the authors doingresearch on how the effort of Iran‟s multilateral diplomacy to take of UN Security Councilpunishment on the president Hassan Rouhani era. This research was conducted with aqualitative description of the approach and use data object Iran‟s multilateral diplomacy to takeof UN Security Council punishment on the era of president Hassan Rouhani on 2013-2015. Theanalysis Technique of data is library research. The result of this research have conclusion Irangovernment still develop their nuclear program even got the punishment from UN SecurityCouncil, Iran government on Hassan Rouhani era by doing multilateral diplomacy with P5+1group to take off the punishment UN Security Council, with the joint agreement between Iranand P5+1 group showing by multilateral diplomacy Iran can solve their nuclear problem withsigning the JCPOA. The authors giving advice for the next authors to continuing about theproblems of Iran Nuclear.Key word : nuclear program, diplomacy, Iran